2015
DOI: 10.14336/ad.2014.1126
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Formula Danggui-Shaoyao-San Promotes Neurogenesis and Angiogenesis in Rat Following Middle Cerebral Artery Occlusion

Abstract: Current studies demonstrated that traditional Chinese herbal formula Danggui-ShaoyaoSan (DSS) is not only used for the treatment of menstrual disorder, but has also found its use in neurological diseases. However, the neuroprotective role of DSS on ischemia-induced brain injury is still unclear. The aim of the present study is to explore the effect of DSS in ischemic brain injury. Total 30 adult female Sprague-Dawley rats underwent 90 min transient middle cerebral artery occlusion (MCAO). DSS (600 mg/kg) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…However DSS has been shown to reduce infract size 24 h post-stroke in a mouse model of MCAO [ 111 ] and to increase cerebral blood flow in the hippocampus in a rat model of global cerebral ischemia [ 112 ]. In a recent study, Ren et al (2015) demonstrated that these post-ischemic protective effects of DSS are associated with focal angiogenesis and neurogenesis via up-regulation of VEGF protein expression and increased eNOS activity [ 113 ]. In a mouse model of ageing, DSS demonstrated a neuroprotective effect by ameliorating oxidative stress and neuronal apoptosis via the Bcl-2/Bax and caspase-3 signalling in the brain [ 114 ].…”
Section: Angiogenic Effects Of Chinese Herbal Medicine In Ischemicmentioning
confidence: 99%
“…However DSS has been shown to reduce infract size 24 h post-stroke in a mouse model of MCAO [ 111 ] and to increase cerebral blood flow in the hippocampus in a rat model of global cerebral ischemia [ 112 ]. In a recent study, Ren et al (2015) demonstrated that these post-ischemic protective effects of DSS are associated with focal angiogenesis and neurogenesis via up-regulation of VEGF protein expression and increased eNOS activity [ 113 ]. In a mouse model of ageing, DSS demonstrated a neuroprotective effect by ameliorating oxidative stress and neuronal apoptosis via the Bcl-2/Bax and caspase-3 signalling in the brain [ 114 ].…”
Section: Angiogenic Effects Of Chinese Herbal Medicine In Ischemicmentioning
confidence: 99%
“…61010; AM Bickford Inc., Wales Center, NY, USA) was used for induction and maintenance. Focal cerebral ischemia was generated using the intraluminal middle cerebral artery occlusion (MCAO) model as described previously [16,21]. Briefly, the right common carotid artery and the right external carotid artery (ECA) were exposed.…”
Section: Animalsmentioning
confidence: 99%
“…However, the time window for this treatment is limited, and the hemorrhage risk is high. 2 The development of a new strategy to increase blood supply to the ischemic area is necessary and urgent.…”
Section: Introductionmentioning
confidence: 99%